REPRESENTASI TOLERANSI KEBERAGAMAN UMAT BERAGAMA DALAM FILM GOOGLE NGULIK RAMADHAN-SATU DALAM KITA (ANALISIS SEMIOTIKA JOHN FISKE) - Fiqie Lavani Melano; Freddy Yusanto (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
Indonesia is an archipelagic country full of wealth and diversity of cultures, races, ethnic groups, beliefs, religions, and many others. Although full of cultural diversity, Indonesia remains one according to its slogan, Bhineka Tunggal Ika which means